Lipid Droplets and Mycobacterium leprae Infection. (12th November 2012) - Elamin, Ayssar A.; Stehr, Matthias; Singh, Mahavir
Abstract : Leprosy is a chronic infectious disease and is a major source of morbidity in developing countries. Leprosy is caused by the obligate intracellular bacterium Mycobacterium leprae, which infects as primary target Schwann cells. Lepromatous leprosy exhibits multiple lesions of the skin, eyes, nerves, and lymph nodes. The sites of infection are characterized by the presence of foamy macrophages, fully packed with lipid droplets (LDs), which are induced by M. leprae . In the last years, it has become evident that M. tuberculosis imports lipids from foamy macrophages and is dependent on fatty acids for growth in infected macrophages. M. leprae seems to have similar mechanisms for scavenging lipids from the host. But due to the inability to culture M. leprae on laboratory media, research progresses only slowly. However, in the last years, substantial progress has been made in the field of lipid metabolism in M. leprae . Herein, we will present and summarize the lipid droplets formation and the metabolism of lipids during M. leprae infection.